2019
DOI: 10.1002/npr2.12052
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related behavioral changes from young to old age in male mice of a C57BL/6J strain maintained under a genetic stability program

Abstract: Aim Aging is thought to coincide with gradual and progressive changes in brain function and behavior over the lifetime. Our previous meta‐analytic study reported age‐related behavioral changes from young to middle age in male C57BL/6J mice. However, the previous study had some limitations that could affect the generalizability of the findings because of the potential influence of genetic and environmental factors on behavior, in addition to a lack of information regarding the behaviors of old‐aged mice. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
109
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 54 publications
22
109
7
Order By: Relevance
“…Such enhanced freezing in both the aged standard and aged exercise groups suggests an age-related enhancement of cued fear memory consolidation, while aging and exercise may also cause enhance acquisition of cued fear memory. These findings are consistent with a recent report of similar increases in freezing with cued fear in aged mice (Shoji & Miyakawa, 2019). The amygdala is a central brain region regulating the acquisition and consolidation of cued fear (Duvarci, Nader, & LeDoux, 2005;Kim et al, 2012;Orsini & Maren, 2012).…”
Section: Aging Effects On Enhanced Conditioned Fear Expressionsupporting
confidence: 93%
“…Such enhanced freezing in both the aged standard and aged exercise groups suggests an age-related enhancement of cued fear memory consolidation, while aging and exercise may also cause enhance acquisition of cued fear memory. These findings are consistent with a recent report of similar increases in freezing with cued fear in aged mice (Shoji & Miyakawa, 2019). The amygdala is a central brain region regulating the acquisition and consolidation of cued fear (Duvarci, Nader, & LeDoux, 2005;Kim et al, 2012;Orsini & Maren, 2012).…”
Section: Aging Effects On Enhanced Conditioned Fear Expressionsupporting
confidence: 93%
“…For the open field task, aging was associated with an increase in time exploring the center of the open field. Crosssectional studies examining exploration on the open field task indicate that exploration is decreased, increased, or not changed with age (Miyagawa et al, 1998;Boguszewski and Zagrodzka, 2002;Torras-Garcia et al, 2005;Bergado et al, 2011;Meyza et al, 2011;Moretti et al, 2011;Shoji and Miyakawa, 2019). The increased exploration of the inner region, as well as the agerelated decrease in time to enter a new environment observed in the current study, may be due to the extensive handling and FIGURE 7 | Composite resting state functional connectivity maps for impaired and unimpaired animals.…”
Section: Discussionmentioning
confidence: 72%
“…However, the overall results in their study indicate a tendency towards increased anxiety-like behavior upon aging. A similar study with a wider range of age showed that aged mice spent more time in the center of the open-field arena than young mice, starting only 10 min after the beginning of the test [57]. Shoji et al thus suggested that, in old-aged mice, anxiety-like behavior might increase compared to young mice when exposed to a novel environment, and then decrease after a long exposure (habituation) to the same environment.…”
Section: Thigmotaxis Remains Unchanged Upon Fipronil Treatmentmentioning
confidence: 95%